Quantifying athlete self-talk - Hardy, J.; Hall, C. R.; Hardy, L. (Journal of Sports Sciences, 2005)
Two studies were conducted. The aims of Study 1 were (a) to generate quantitative data on the content of athletes' self-talk and (b) to examine differences in the use of self-talk in general as well as the functions of self-talk in practice and competition settings. Differences in self-talk between the sexes, sport types and skill levels were also assessed. Athletes (n=295, mean age=21.9 years) from a variety of sports and competitive levels completed the Self-Talk Use Questionnaire (STUQ), which was developed specifically for the study. In Study 1, single-factor between-group multivariate analyses of variance revealed significant differences across sex and sport type for the content of self-talk. Mixed-model multivariate analyses of variance revealed overall greater use of self-talk, as well as increased use of the functions of self-talk, in competition compared with practice. Moreover, individual sport athletes reported greater use of self-talk, as well as the functions of self-talk, than their team sport counterparts. In Study 2, recreational volleyball players (n=164, mean age=21.5 years) completed a situationally modified STUQ. The results were very similar to those of Study 1. That the content of athlete self-talk was generally positive, covert and abbreviated lends support to the application of Vygotsky's (1986) verbal self-regulation theory to the study of self-talk in sport. Researchers are encouraged to examine the effectiveness of self-talk in future studies.